Measure the relationship between inflation and the exchange rate in the formulation of Monetary policy in Iraq for the period 1990-2018 - Mutlag, Haitham Hameed; Hasim, Suad Qasim; Al-Daghir, Mahmoud Mohamed (Journal of Economics and Administrative Sciences, 2021)
Due to the importance of the relationship between the phenomenon of inflation and the exchange rate in the formulation of monetary policy in Iraq, the exchange rate plays a strategic role in limiting the inflation caused by the monetary expansion due to government spending, as a point of a view, the inefficiency of interest to achieve the monetary market balance and stability of the general level of prices as an overall goal of monetary policy in Iraq, the exchange rate has emerged as a brake on inflation in Iraq, as the research found that the monetary authority in the period 2003-2018 provided a methodical development in the formulation of monetary policy towards realizing the effects of inflation and seeking to develop a diagnosis of a nominal fixer that is suitable for managing inflation rates as an alternative to the interest that does not work.       Therefore, the research tried to diagnose the relationship between inflation and exchange rate and its real significance in formulation the goal of stability in growth rates at the general level of prices, by regulating the money supply flows within the framework of the Central Bank’s management, the purchasing power of the Iraqi dinar through its monetary operations in organizing the movement of the monetary basis to reach actual inflation Controlled within the target. As the research concluded the efficiency of the exchange rate, a nominal Anchor of the monetary policy. Since the goal of monetary policy is to ensure the stability of the real value of the local currency, achieving stability of annual inflation rates will be through the stability of the exchange rate